Crystal structure of bis[μ2-(pyrrolidine-1-carbodithioato-κS:κS,κS′)]-bis(triethylphosphine-κP)disilver(I), C22H46Ag2N2P2S4 - Tan, Yi Jiun *; Yeo, Chien Ing *; Halcovitch, Nathan R.; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C22H46Ag2N2P2S4, triclinic, P1̄ (no. 2), a = 10.2008(3) Å, b = 12.2058(3) Å, c = 13.2466(4) Å, α = 88.155(2)°, β = 87.256(2)°, γ = 69.324(2)°, V = 1541.12(8) Å3, Z = 2, R gt(F) = 0.0237, wR ref(F 2) = 0.0621, T = 100(2) K.